Phenomenological engagement as pedagogical impetus in career counselling education - Conradie, Karlien (Critical Studies in Teaching and Learning, 2024)
This article aims to present the author’s understanding of how a phenomenologically concerned pedagogy can offer an antidote to the influence that a post-industrial consumerist culture has on career counselling education. In the age of mediatisation, surges of endless commercialisation and consumption has evolved in a crisis of relationality, characterised by ecological fragmentation and disconnectedness. The present article explains how an overly utilitarian mindset reinforces an instrumentalist approach to career counselling, inhibiting student educational psychologists’ capacity for being conscious of the embodied lifeworld situation of a person engaging in career counselling. The embodied lifeworld situation refers to an ecologically integrated person reality, intricately anchored in time, space, and historicity. A pedagogical approach is needed that forefronts phenomenological engagement – relational being and knowing - as a way of conserving students’ ability for embodied consciousness.